Exposure to sustainable mineral fibers as a reinforcement in polymer composites - Jagadeesh, Praveenkumara; Rangappa, Sanjay Mavinkere; Siengchin, Suchart (Journal of Fibers and Polymer Composites, 2025)
Editor's Corner